Hadist Dan Tafsir Bi al-Ma’Tsur: Telaah Tafsir al-Thabari - Dini Kartika; Uswatun Hasanah (Jurnal Teologi Islam, 2025)
This research is to examine Tafsir al-Thabari Hadith and Tafsir Bi al-Ma'Tsur:. The results of the analysis found that Thabari has taken a very important methodological step, where the interpretation does not only contain explanations of narrations and atsar, which is often called tafsir bil ma'tsur (tafsir with history), but with Thabari's work, the interpretation has been mixed with analytical studies that do not deviate from the path of truth. The interpretation model produced by Thabari is considered by some specialist scholars as a new work. They say that Ibn Jarir Ath-Thabari's interpretation has become a scientific interpretation that tends to prioritize the analytical side rather than the atsar side. As for assessing the validity of Imam al-Thabari's hadith that he used in interpreting the verses of the Qur'an, it can be seen in the footnotes in the book Tafsir Jami' al-Bayan Ta'wil al-Qur'an Imam al-Thabari explains in full regarding the hadith he quoted.